Cellular and Molecular Biomarkers Predictive of Response to Immunotherapy in Acute Myeloid Leukemia - Wiatrowski, Kyle; Kim, Tae Hee; Przespolewski, Amanda (Frontiers in Oncology, 2022)
Immunotherapy has without question revolutionized the treatment of both hematologic and solid malignancies. Over the last several years novel strategies are being developed to incorporate these groundbreaking therapies into the care of patients with AML. Here we present an overview of the recent developments in immunotherapy for AML with a focus on biomarkers of response. Topics reviewed include antibody drug conjugates, BiTEs, DARTs, and checkpoint inhibitors as well as the development of biomarkers predictive of response in each class.